2014
DOI: 10.1002/ejic.201301363
|View full text |Cite
|
Sign up to set email alerts
|

4‐(1‐Amino‐5‐aminotetrazolyl)methyleneimino‐3‐methylfuroxan and Its Derivatives: Synthesis, Characterization, and Energetic Properties

Abstract: The condensation reaction of 4-formyl-3-methylfuroxan with 1,5-diaminotetrazole led to 4-(1-amino-5-aminotetrazolyl)methyleneimino-3-methylfuroxan (1) in high yield. Its structure was confirmed by an X-ray diffraction study. 4-(1-Amino-5-nitriminotetrazolyl)methyleneimino-3-methylfuroxan (2) was obtained through the nitration of 1 with 100 % HNO 3 . The nitrogen-rich salts of 2 with bases such as 1amino-1,2,3-triazole (3), 4-amino-1,2,4-triazole (4), and 3amino-1,2,4-triazole (5) were synthesized and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The structure of MGBTO was characterized by FTIR, 1 H NMR, 13 C NMR, EA, and single crystal X-ray diffraction. As shown in Figure 1, the IR spectrum of MGBTO shows a sharp, strong band at 1689 cm -1 .…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of MGBTO was characterized by FTIR, 1 H NMR, 13 C NMR, EA, and single crystal X-ray diffraction. As shown in Figure 1, the IR spectrum of MGBTO shows a sharp, strong band at 1689 cm -1 .…”
Section: Characterizationmentioning
confidence: 99%
“…The tetrazole ring and its derivatives have attracted extensive interest because of their unique and excellent properties, such as high nitrogen content, high formation enthalpy, and good stability [8]. Among all of the strategies used to improve the detonation performance of energetic materials, the use of N-oxides is a special approach that facilitates the achievement of oxygen balance [8][9][10][11][12][13][14][15]. Fischer and his coworkers synthesized a series of 1H,1′H-5,5′-bistetrazole-1,1′-diolate (BTO) salts [8,16] and showed that the excellent performance of dihydroxylammonium 1H,1′H-5,5′-bistetrazole-1,1′diolate (TKX-50) is comparable with that of CL-20.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have since synthesized a series of metallic or nonmetallic salts of N 5 − via ion exchange reactions [ 12 , 13 ]. Compounds containing all-nitrogen structural fragments, such as N8 (1,1′-azobis-1,2,3-triazole), N10 (1,1′-azobis(5-methyltetrazole)) and N11 (1,1′-(triaz-1-ene-1,3-diyl)bis(1H-tetrazol-5-amine)), have been synthesized successively [ 14 , 15 ], providing references for the preparation of all-nitrogen materials.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the aspect of energetic salts, as shown in Scheme 1, anions containing the furoxan ring and other energetic groups or backbones bearing acidic protons, have been investigated. [8][9][10][11] In 2012, Z. Zhou et al synthesized a series of energetic monoanionic and dianionic salts of 3,4-bis(1H-tetrazol-5-yl)furoxan with good thermal stabilities and rather high densities. 8,9 In the next year, nine energetic salts based on 4-nitro-3-(5-tetrazolate)furoxan anion were also synthesized and fully characterized by them.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, three energetic salts based on furoxanyl functionalized tetrazolate anion were synthesized and well characterized. 11 On the other hand, to the best of our knowledge, few energetic salts based on furoxanyl functionalized cation has been reported in the literature. 12 In the present work, a new family of energetic salts based on a furoxanyl functionalized aminoguanidinium cation (FAG cation) was synthesized.…”
Section: Introductionmentioning
confidence: 99%